Analisis Kepuasan Terhadap Kualitas Pelayanan Bimbingan Belajar Pada Kursuspintar Menggunakan Metode Servqual - Esa Listian Habib; Eva Zuraidah (Journal of Information System Research (JOSH), 2023)
In providing the best service to students, there are several CoursePintar supervisors who have competencies according to their fields of expertise, this aims to create a good quality of service because good service quality will produce student satisfaction feedback. However, KursusPintar does not yet have a measurable evaluation in providing teaching and learning services, to find out the quality of tutoring services at KursusPintar, researchers evaluate the quality of services, teachers, facilities, tutoring places and information on course fees on the web is not displayed on KursusPintar, which must be inquired through the Whatsapp admin contact. Measurements were carried out using the Servqual method which then obtained 98 respondents resulting from the slovin method. Then a validity test was carried out with a Pearson N-2 correlation at a significance of 0.05 obtained r table 0.202. Then test the reability with Cronbach's Alpha with a value of 0.7. Measurement with servqual with 5 dimensions of service quality, namely tangible, reliability, responsiveness, assurance and empathy, which is then displaced based on Importance Performance Analisys (IPA) with the best gap value results that need to be maintained, namely Tangible (Physical Evidence) with a gap value of -0.078 where KursusPintar understands the facilities needed by KursusPintar service users and the highest priority gap that needs to be improved is Assurance (Guarantee) with a gap value of -0.374 where users of KursusPintar services still feel that learning activities at KursusPintar are still not conducive so that learning materials cannot be received properly